The Analysis of Ease of Use, Trust, and Website Quality towards Purchasing Decision in Lazada.co.id - Dadang Suhardi; Nuryanti Taufik (Indonesian Journal Of Business And Economics, 2018)
This research aims to find out the impact of ease of use, trust, website quality towards purchasing decision in online trading site “Lazada.co.id”. The quantitative research is conducted through the implementation of survey. The data collection techniques used in this study with a questionnaire method is distributed to respondents in Ciamis District who had transaction in Lazada.co.id. The number of the sample gained in this research is the population of Ciamis district with the coverage of 100 respondents. The sampling technique used is non-probability sampling with purposive sampling method. The analysis tool applied in this research is by the use of simple linear Regression and multiple linear regression with SPSS 23. The result of the research indicates that the ease of use, trust, and website quality influenced positive and significance towards purchasing decision partially and simultaneously. In this research, website quality gives stronger influence towards purchasing decision comparing with ease of use and trust.